Al2O3-RE2O3 synergistically modified high-temperature water and oxygen erosion resistant silicon carbide ceramic-based composite material and preparation method thereof
By introducing RE2O3 and Al2O3 into the SiCf/SiC composite material, the RE2Si2O7 crystalline phase and the Al-Si-O glass phase are generated, which solves the problem of oxidative erosion of the material in a high-temperature water-oxygen environment and significantly improves the water-oxygen erosion resistance of the material.
Patent Information
- Application Number
- CN202510174919.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-18
AI Technical Summary
Existing SiCf/SiC composite materials are susceptible to oxidation and erosion in high-temperature water and oxygen environments, resulting in a degradation of service performance. Existing modified materials such as RE2Si2O7 have poor fluidity at high temperatures and cannot effectively repair material defects.
RE2O3 and Al2O3 are introduced through slurry impregnation. During the oxidation of water and oxygen, the RE2Si2O7 crystalline phase and Al-Si-O glass phase are formed in situ to modify the silicon carbide ceramic matrix composite material.
The generated RE2Si2O7 crystalline phase improves the high-temperature water oxygen stability of the material, and the Al-Si-O glass phase repairs the material's defects, improves the density of the oxide layer, and significantly improves the water oxygen corrosion resistance of the material.
Smart Images

Figure CN119661227A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicon carbide ceramic-based composite materials, and relates to an Al2O3-RE2O3 synergistically modified high-temperature water-oxygen corrosion-resistant silicon carbide ceramic-based composite material and a preparation method thereof. Background Art
[0002] The continuous development of the aviation field has brought higher challenges to the performance of aircraft engines. The hot end components of aircraft engines need to withstand harsh environments such as high temperature, pressure, gas scouring, water and oxygen corrosion during service. Continuous silicon carbide fiber reinforced silicon carbide (SiC f / SiC) composite materials have become the preferred thermal structure material for the new generation of aircraft engines due to their advantages such as high temperature resistance, light weight, high strength and non-brittle fracture.
[0003] In actual service environment, SiC f The SiO2 oxide layer generated by oxidation on the surface of the SiC composite material reacts with H2O in the environment to form volatile Si(OH)4. The dense oxide layer gradually becomes loose and even peels off, thereby accelerating the oxidation corrosion of the material. f / SiC composite material service performance rapidly declines. In order to improve the f To improve the service life of SiC composites, it is necessary to introduce a water-oxygen stable phase into the matrix to modify the composite. Rare earth disilicate (RE2Si2O7) has excellent high-temperature water-oxygen stability and matches the thermal expansion coefficient of the SiC matrix. f Candidate modified materials for improving the water and oxygen corrosion resistance of SiC / SiC composites. References [1-2] ([1] Fang He, J Eur Ceram Soc, 2021, 16(41): 93-100; [2] Peng Wang, J Inorg Mater, 2019, 34: 904-908) have reported the direct introduction of rare earth silicates into the matrix to improve the water and oxygen corrosion resistance of composites. However, RE2Si2O7 has poor fluidity at high temperatures and cannot heal the intrinsic defects of the material and the defects caused by water and oxygen corrosion. SiC f / SiC composites will still be damaged by water and oxygen media. Therefore, the introduction of RE2Si2O7 and the addition of self-healing phase synergistic modification is a way to improve the SiC f / SiC composites have a more promising approach to improving the water and oxygen corrosion resistance.
[0004] Patent No. CN116891384A discloses a SiBCN-RE2Si2O7 synergistically modified silicon carbide ceramic-based composite material and its preparation method. RE2Si2O7 and SiBCN are directly introduced into the matrix of the silicon carbide ceramic-based composite material through the precursor impregnation and cracking process, and the self-healing effect of SiBCN and the RE2Si2O7 protective layer are used to improve the water and oxygen corrosion resistance of the composite material. However, B2O3 generated by the oxidation of SiBCN will volatilize rapidly under high-temperature water and oxygen conditions, which is not conducive to the high-temperature water and oxygen stability of the material.
[0005] Patent No. CN116283318A and Patent No. CN113307660A both directly introduce RE2O3-Al2O3-SiO2 glass phase as a self-healing phase. Compared with B2O3, it has stronger high-temperature water and oxygen stability and can heal cracks and holes. However, directly introducing a large amount of glass phase into the matrix will greatly reduce the high-temperature creep resistance of the composite material.
[0006] Patent No. CN117923928A discloses a ceramic-based composite material modified by a multiphase oxide ceramic and its preparation method, which introduces high entropy rare earth disilicate by slurry impregnation, and then introduces a glass phase by melt infiltration and achieves densification, thereby improving the material's resistance to water and oxygen erosion. However, a large amount of glass phase will remain in the material matrix, which seriously affects the material's high-temperature creep performance. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides an Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic-based composite material and a preparation method thereof.
[0008] On the one hand, the present invention provides a method for preparing an Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic matrix composite material, comprising: (1) Mixing SiC powder, RE2O3 powder, Al2O3 powder, carbon black, a binder and a solvent to obtain a mixed slurry; (2) immersing the fiber preform into the mixed slurry, drying, curing, and pyrolyzing to obtain a carbon-containing porous preform; (3) The carbon-containing porous preform is subjected to silicon reactive infiltration treatment to obtain the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic matrix composite material.
[0009] The inventor discovered in the early research and development process that only RE2O3 is introduced into the silicon carbide ceramic-based composite material, and RE2Si2O7 crystalline phase is generated during the water-oxygen oxidation process. Although it has excellent high-temperature water-oxygen stability and can protect the internal matrix from corrosion, it cannot repair the defects caused by water-oxygen corrosion and the intrinsic defects of the material. For this reason, in the present invention, RE2O3 and Al2O3 are simultaneously introduced through slurry impregnation, and in the water-oxygen oxidation process, they react with SiO2 in the oxide layer to generate RE2Si2O7 crystalline phase in situ and generate Al-Si-O glass phase in reduction position. Among them, RE2Si2O7 crystalline phase has excellent high-temperature water-oxygen stability, can protect the internal matrix from corrosion, Al-Si-O glass phase can heal the defects caused by water-oxygen corrosion, improve the density of the oxide layer, promote the aggregation of RE2Si2O7 on the surface of the oxide layer, and further slow down the diffusion of water-oxygen medium to the inside, thereby better improving the water-oxygen corrosion resistance of the material. On the other hand, the present invention can also avoid the formation of RE-Al-Si-O glass during the oxidation process by designing a RE2O3-Al2O3 / SiC matrix phase of a specific composition in the matrix of the composite material. Compared with RE-Al-Si-O glass, the water-oxygen corrosion-resistant phase (RE2Si2O7 crystalline phase) and the self-healing phase (Al-Si-O glass phase) generated by the present invention work synergistically to better inhibit water-oxygen corrosion. In addition, since the Al-Si-O glass phase is only formed in the oxide layer, the matrix still maintains excellent high-temperature creep resistance, thereby realizing the water-oxygen resistance-structure integrated design of the composite material.
[0010] Preferably, in step (1), the RE2O3 powder is selected from one of Y2O3, Yb2O3, La2O3, Lu2O3, Ce2O3, Er2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3, Dy2O3, and Ho2O3.
[0011] Preferably, the binder is at least one of polyvinyl alcohol, polyvinyl butyral or polymethyl methacrylate; and the solvent is at least one of ethanol, isopropanol or xylene.
[0012] Preferably, in step (1), the particle size of the SiC powder is 0.01 to 10 μm, preferably 0.5 to 5 μm; the particle size of the RE2O3 powder is 0.01 to 10 μm, preferably 0.5 to 5 μm; the particle size of the Al2O3 powder is 0.01 to 10 μm, preferably 0.5 to 5 μm; the particle size of the carbon black is 0.001 to 1 μm, preferably 0.01 to 0.1 μm.
[0013] Preferably, in step (1), the mass ratio of SiC powder, RE2O3 powder, Al2O3 powder, carbon black, binder and solvent in the mixed slurry is (30-70): (10-30): (5-10): (10-30): (5-10): (35-65).
[0014] Preferably, in step (2), the fiber preform is a silicon carbide fiber preform; preferably, the structure of the silicon carbide fiber preform is at least one of a two-dimensional stitched braided structure, a three-dimensional needle-punched braided structure, a three-dimensional four-way braided structure, and a three-dimensional five-way braided structure; more preferably, an interface layer is deposited on the surface of the silicon carbide fiber preform; the interface layer is one of pyrolytic carbon or boron nitride; and the thickness of the interface layer is 0.1 to 1.0 μm.
[0015] Preferably, in step (2), the slurry is impregnated by at least one of ultrasonic impregnation, vibration impregnation and negative pressure impregnation.
[0016] Preferably, in step (2), the curing temperature is 80 to 300°C and the curing time is 0.5 to 2 hours; The pyrolysis temperature is 500-1000°C and the time is 0.5-2 hours.
[0017] Preferably, in step (2), the open porosity of the carbon-containing porous preform is 5% to 30%.
[0018] Preferably, in step (3), the temperature of the silicon reactive infiltration treatment is 1400-1800° C., and the time is 0.1-5 hours.
[0019] On the other hand, the present invention provides an Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic-based composite material prepared according to the above-mentioned preparation method, wherein the volume fraction of the silicon carbide fiber preform is 10-40%, the volume fraction of the SiC matrix is 30-60%, the volume fraction of the RE2O3 phase is 2-10%, and the volume fraction of the Al2O3 phase is 3-6%.
[0020] Preferably, the Al2O3-RE2O3 synergistically modified high temperature water-oxygen corrosion-resistant silicon carbide ceramic-based composite material has a strength retention rate of 77.0-90.0% after water-oxygen oxidation at 1400°C for 100 h, and the thickness of the oxidation layer after water-oxygen oxidation is 10-15 μm.
[0021] Beneficial Effects (1) In the present invention, the modified components (RE2O3, Al2O3) are introduced into the matrix of the silicon carbide ceramic-based composite material by slurry impregnation. The method is simple and efficient. The introduced RE2O3-Al2O3 will react with SiO2 in the oxide layer during the water-oxygen oxidation process to generate RE2Si2O7 crystalline phase and Al-Si-O glass phase in situ. Among them, the RE2Si2O7 crystalline phase has excellent high-temperature water-oxygen stability and can inhibit the damage of the water-oxygen medium to the material. The Al-Si-O glass phase can heal the defects caused by water-oxygen corrosion, improve the density of the oxide layer, promote the aggregation of RE2Si2O7 on the surface of the oxide layer, and further slow down the diffusion of the water-oxygen medium into the interior, thereby better improving the material's resistance to water-oxygen corrosion; (2) The present invention avoids the formation of RE-Al-Si-O glass by designing a RE2O3-Al2O3 / SiC matrix phase of a specific composition in the composite matrix. The water-oxygen corrosion-resistant phase (RE2Si2O7 crystalline phase) and the self-healing phase (Al-Si-O glass phase) work together to improve the high-temperature water-oxygen corrosion resistance of the silicon carbide ceramic-based composite material. In addition, since the Al-Si-O glass phase is only formed in the oxide layer, the matrix still maintains excellent high-temperature creep resistance, thereby realizing the water-oxygen resistance-structure integrated design of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The preparation route map of the RE2O3-Al2O3 synergistically modified silicon carbide ceramic-based composite material resistant to high temperature water and oxygen corrosion of the present invention; Figure 2 The RE2O3-Al2O3 modified SiC in Example 1 f Microstructure of / SiC composites; Figure 3 The RE2O3-Al2O3 modified SiC in Example 1 f Surface morphology of / SiC composites; Figure 4 The RE2O3-Al2O3 modified SiC in Example 1 f SEM images of / SiC composites after 1400 ℃ water-oxygen immersion for 100 h, where a is the microscopic morphology and b is the oxygen corrosion depth; Figure 5 The RE2O3-Al2O3 modified SiC in Example 1 f / SiC composite material and unmodified SiC in comparative example 1 f Strength retention rate of / SiC composites after 100 h of water-oxygen treatment; Figure 6 For the YE2O3 modified SiC in Comparative Example 3 f Microstructure of / SiC composite material after 1400 ℃ water oxygen for 100 h; Figure 7 For RE2O3-Al2O3 modified SiC in Comparative Example 6 f Microstructure of the / SiC composite material after being exposed to water and oxygen at 1400 ℃ for 100 h. DETAILED DESCRIPTION
[0023] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.
[0024] In the present invention, RE2O3-Al2O3 introduced by slurry impregnation will react with SiO2 in the oxide layer to generate RE2Si2O7 crystalline phase and Al-Si-O glass phase in situ during the water-oxygen oxidation process. Among them, the RE2Si2O7 crystalline phase has excellent high-temperature water-oxygen stability, can protect the internal matrix from corrosion, and the generated Al-Si-O glass phase can heal the defects caused by water-oxygen corrosion, improve the density of the oxide layer, promote the aggregation of RE2Si2O7 on the surface of the oxide layer, and further slow down the diffusion of water-oxygen medium to the inside, so as to better improve the water-oxygen corrosion resistance of the material. By designing a RE2O3-Al2O3 / SiC matrix phase with a specific composition in the composite matrix, the formation of RE-Al-Si-O glass is avoided during the oxidation process. Compared with RE-Al-Si-O glass, the water-oxygen corrosion-resistant phase (RE2Si2O7 crystalline phase) and the self-healing phase (Al-Si-O glass phase) work synergistically to better inhibit water-oxygen corrosion. In addition, since the Al-Si-O glass phase is only formed in the oxide layer, the matrix still maintains excellent high-temperature creep resistance, thereby realizing the water-oxygen-resistant-structure integrated design of the composite material.
[0025] Specifically, the present invention regulates the mass ratio of RE2O3 to Al2O3 within the range of 1 to 6, so that RE2Si2O7 crystalline phase and Al-Si-O glass phase are generated in situ in the oxide layer, and RE-Al-Si-O glass is not directly formed. If the mass ratio of RE2O3:Al2O3 is greater than 6, too little Al2O3 is not conducive to the formation of Al-Si-O glass, affecting the self-healing performance of the material. If the mass ratio of RE2O3:Al2O3 is less than 1, too much Al2O3 leads to a tendency to directly generate RE-Al-Si-O glass during the oxidation process. The water-oxygen erosion resistance of RE-Al-Si-O glass is not as good as that of RE2Si2O7 crystalline phase, and the water-oxygen erosion resistance of the material will also be significantly reduced.
[0026] The following is an exemplary description of the preparation method of the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic matrix composite material provided by the present invention (such as Figure 1 as shown).
[0027] SiC powder, RE2O3 powder (RE = Y, Yb, La, Lu, etc.), Al2O3 powder, carbon black, a binder and a solvent are mixed to obtain a mixed slurry. The particle size of the SiC powder is 0.01 to 10 μm, preferably 0.5 to 5 μm; the particle size of the RE2O3 powder is 0.01 to 10 μm, preferably 0.5 to 5 μm; the particle size of the Al2O3 powder is 0.01 to 10 μm, preferably 0.5 to 5 μm; the particle size of the carbon black is 0.001 to 1 μm, preferably 0.01 to 0.1 μm. The binder is at least one of polyvinyl alcohol, polyvinyl butyral or polymethyl methacrylate; the solvent is at least one of ethanol, isopropanol or xylene.
[0028] In an optional embodiment, the RE2O3 powder is selected from one of Y2O3, Yb2O3, La2O3, Lu2O3, Ce2O3, Er2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3, Dy2O3, and Ho2O3.
[0029] In an optional embodiment, the mass ratio of SiC powder, RE2O3 powder, Al2O3 powder, carbon black, binder and solvent in the mixed slurry is (30-70): (10-30): (5-10): (10-30): (5-10): (35-65).
[0030] The fiber preform is immersed in the mixed slurry, and then dried, solidified, and pyrolyzed to obtain a carbon-containing porous preform. The obtained carbon-containing porous preform has an open porosity of 5% to 30%.
[0031] In an optional embodiment, the fiber preform is a silicon carbide fiber preform; preferably, the structure of the silicon carbide fiber preform is at least one of a two-dimensional stitched braided structure, a three-dimensional needle-punched braided structure, a three-dimensional four-way braided structure, and a three-dimensional five-way braided structure; more preferably, an interface layer is deposited on the surface of the silicon carbide fiber preform; the interface layer is one of pyrolytic carbon or boron nitride.
[0032] In an optional embodiment, the slurry is impregnated by at least one of ultrasonic impregnation, vibration impregnation, and negative pressure impregnation.
[0033] In an optional embodiment, the curing temperature is 80-300°C, and the curing time is 0.5-2 hours. The pyrolysis temperature is 500-1000°C, and the time is 0.5-2 hours.
[0034] The carbon-containing porous preform is subjected to silicon reactive infiltration treatment to obtain the Al2O3-RE2O3 synergistically modified high-temperature water-oxygen corrosion-resistant silicon carbide ceramic-based composite material.
[0035] In an optional embodiment, the silicon reactive infiltration treatment is carried out at a temperature of 1400 to 1800° C. and for a time of 0.1 to 5 hours.
[0036] The Al2O3-RE2O3 synergistically modified high-temperature water-oxygen corrosion-resistant silicon carbide ceramic-based composite material prepared by the preparation method of the present invention comprises the following: the volume fraction of the silicon carbide fiber preform is 10-40%, the volume fraction of the SiC matrix is 30-60%, the volume fraction of the RE2O3 phase is 2-10%, and the volume fraction of the Al2O3 phase is 3-6%.
[0037] The following examples are further cited to explain the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are only an example within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description of this article, and are not limited to the specific values exemplified below. The parameters of high-temperature water oxygen are: the heating and cooling rates are controlled at 1 to 10°C / min, and the gas flow rate is controlled at 100 to 1000 ml / min (oxygen: water vapor molar ratio = 0.3 to 15).
[0038] Example 1 (1) SiC powder, Y2O3 powder, Al2O3 powder, carbon black, polyvinyl alcohol (binder) and ethanol (solvent) are ball-milled to obtain a stable slurry; wherein the mass ratio of SiC powder, Y2O3 powder, Al2O3 powder, carbon black, polyvinyl alcohol (binder) and ethanol is 40: 15: 5: 10: 5: 55; the average particle size of SiC powder is 2 μm, the average particle size of Y2O3 powder is 2 μm, the average particle size of Al2O3 powder is 2 μm, and the average particle size of carbon black is 0.1 μm; (2) The slurry was introduced into the silicon carbide fiber preform (three-dimensional needle-punched woven structure) by vibration impregnation. Before impregnation, a BN interface phase was deposited on the surface of the fiber preform. The thickness of the BN interface layer was 0.5 μm. After impregnation, the carbon-containing porous preform was obtained by drying, curing, and pyrolysis. The curing temperature was 200 °C for 1 hour; the pyrolysis temperature was 700 °C for 1 hour; the open porosity of the porous preform was 20%; (3) The porous preform is subjected to silicon reactive infiltration treatment to obtain an Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic matrix composite material; wherein the reactive infiltration temperature is 1600°C and the time is 2 hours.
[0039] After testing, the strength retention rate of the Al2O3-RE2O3 synergistically modified high temperature water-oxygen corrosion-resistant silicon carbide ceramic matrix composite material prepared in Example 1 after water-oxygen oxidation at 1400°C for 100 h was 85.2% (as shown in Figure 1). Figure 5 As shown in Figure 2), the thickness of the oxidation layer after water and oxygen is 10.8 μm (as shown in Figure 2). Figure 4 (as shown in a).
[0040] Example 2
[0041] The preparation process of the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic matrix composite material in Example 2 is similar to that in Example 1, with the only difference being that in step (1), the average particle size of the SiC powder is 5 μm.
[0042] After testing, the Al2O3-RE2O3 synergistically modified high temperature water-oxygen corrosion-resistant silicon carbide ceramic-based composite material prepared in Example 2 has a strength retention rate of 80.6% after water-oxygen oxidation at 1400°C for 100 h, and the thickness of the oxidation layer after water-oxygen oxidation is 13.5 μm.
[0043] Example 3
[0044] The preparation process of the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic-based composite material in this Example 3 refers to Example 1, with the only difference being that in step (1), the mass ratio of SiC powder, Y2O3 powder, Al2O3 powder, carbon black, polyvinyl alcohol (binder) and ethanol is 45:15:5:10:5:55.
[0045] After testing, the Al2O3-RE2O3 synergistically modified high temperature water-oxygen corrosion-resistant silicon carbide ceramic-based composite material prepared in Example 3 has a strength retention rate of 83.5% after water-oxygen oxidation at 1400°C for 100 h, and the thickness of the oxidation layer after water-oxygen oxidation is 11.3 μm.
[0046] Example 4
[0047] The preparation process of the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic-based composite material in this Example 4 refers to Example 1, with the only difference being that in step (1), the Y2O3 powder is replaced by Yb2O3 powder.
[0048] After testing, the Al2O3-RE2O3 synergistically modified high temperature water-oxygen corrosion-resistant silicon carbide ceramic-based composite material prepared in Example 4 has a strength retention rate of 82.6% after water-oxygen oxidation at 1400°C for 100 h, and the thickness of the oxidation layer after water-oxygen oxidation is 11.7 μm.
[0049] Example 5
[0050] The preparation process of the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic matrix composite material in this embodiment 5 refers to that in embodiment 1, the only difference is that in step (2), two-dimensional silicon carbide fiber cloth is selected, and the fiber cloth is laminated after impregnation and then cured.
[0051] After testing, the strength retention rate of the Al2O3-RE2O3 synergistically modified high temperature water oxygen corrosion resistant silicon carbide ceramic matrix composite material prepared in Example 5 after water oxygen oxidation at 1400°C for 100 h was 78.9%, and the thickness of the oxidation layer after water oxygen was 13.8 μm. Compared with Example 1, the strength retention rate of the Al2O3-RE2O3 synergistically modified high temperature water oxygen corrosion resistant silicon carbide ceramic matrix composite material after water oxygen oxidation at 1400°C for 100 h was significantly reduced. This is because the two-dimensional fiber cloth is prone to leave some holes between the layers during the lamination process. These holes will cause some oxidizing media to erode into the material faster, so the strength retention rate decreases more significantly.
[0052] Example 6
[0053] The preparation process of the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic-based composite material in Example 6 refers to Example 1, with the only difference being that in step (2), the curing temperature is 100°C.
[0054] After testing, the Al2O3-RE2O3 synergistically modified high temperature water-oxygen corrosion-resistant silicon carbide ceramic-based composite material prepared in Example 6 has a strength retention rate of 81.9% after water-oxygen oxidation at 1400°C for 100 h, and the thickness of the oxidation layer after water-oxygen oxidation is 12.3 μm.
[0055] Example 7
[0056] The preparation process of the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic-based composite material in this Example 7 refers to Example 1, with the only difference being that in step (2), the pyrolysis temperature is 800°C.
[0057] After testing, the Al2O3-RE2O3 synergistically modified high temperature water-oxygen corrosion-resistant silicon carbide ceramic-based composite material prepared in Example 7 has a strength retention rate of 84.2% after water-oxygen oxidation at 1400°C for 100 h, and the thickness of the oxidation layer after water-oxygen oxidation is 11.4 μm.
[0058] Example 8
[0059] The preparation process of the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic matrix composite material in Example 8 refers to Example 1, with the only difference being that in step (3), the reaction infiltration temperature is 1700°C.
[0060] After testing, the Al2O3-RE2O3 synergistically modified high temperature water-oxygen corrosion-resistant silicon carbide ceramic-based composite material prepared in Example 8 had a strength retention rate of 82.6% after water-oxygen oxidation at 1400°C for 100 h, and the thickness of the oxidation layer after water-oxygen oxidation was 12.1 μm.
[0061] Example 9
[0062] The preparation process of the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic matrix composite material in Example 9 refers to Example 1, with the only difference being that in step (3), the reaction infiltration time is 1 h.
[0063] After testing, the Al2O3-RE2O3 synergistically modified high temperature water-oxygen corrosion-resistant silicon carbide ceramic-based composite material prepared in Example 9 had a strength retention rate of 80.3% after water-oxygen oxidation at 1400°C for 100 h, and the thickness of the oxidation layer after water-oxygen oxidation was 13.2 μm.
[0064] Comparative Example 1
[0065] The preparation process of the silicon ceramic-based composite material in this comparative example 1 refers to that in Example 1, with the only difference being that in step (1), no Y2O3 powder and no Al2O3 powder are introduced.
[0066] After testing, the strength retention rate of the silicon carbide ceramic-based composite material prepared in this comparative example 1 after water-oxygen oxidation at 1400°C for 100 h was 57.6%, and the thickness of the oxidation layer after water-oxygen oxidation was 32.5 μm.
[0067] Comparative Example 2
[0068] The preparation process of the silicon ceramic-based composite material in Comparative Example 2 refers to that in Example 1, with the only difference being that in step (1), only Al2O3 powder is introduced.
[0069] After testing, the strength retention rate of the silicon carbide ceramic-based composite material prepared in this comparative example 2 after water-oxygen oxidation at 1400°C for 100 h was 65.9%, and the thickness of the oxidation layer after water-oxygen oxidation was 25.9 μm.
[0070] Comparative Example 3
[0071] The preparation process of the silicon ceramic-based composite material in this comparative example 3 refers to that in Example 1, with the only difference being that in step (1), only Y2O3 powder is introduced.
[0072] After testing, the strength retention rate of the silicon carbide ceramic-based composite material prepared in this comparative example 3 after water-oxygen oxidation at 1400°C for 100 h was 74.6%, and the thickness of the oxidation layer after water-oxygen oxidation was 18.8 μm (such as Figure 6 This is because although the introduction of Y2O3 allows the material to generate RE2Si2O7 crystalline phase in situ during the water-oxygen oxidation process, which can protect the internal matrix from corrosion, it cannot repair the defects caused by water-oxygen corrosion and the intrinsic defects of the material. The water-oxygen medium can diffuse rapidly into the material through these defects, accelerating the water-oxygen corrosion of the material and making the oxide layer thicker.
[0073] Comparative Example 4
[0074] The preparation process of the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic-based composite material in this comparative example 4 refers to Example 1, with the only difference being that in step (1), the mass ratio of SiC powder, Y2O3 powder, Al2O3 powder, carbon black, polyvinyl alcohol (binder) and ethanol is 25:35:20:5:4:70.
[0075] After testing, the Al2O3-RE2O3 synergistic modified high temperature water-oxygen corrosion resistant silicon carbide ceramic matrix composite material prepared in this comparative example 4 has a strength retention rate of only 60.5% after water-oxygen oxidation at 1400°C for 100 h. This is because the introduction of too much Y2O3 and Al2O3 will consume too much SiO2, which is not conducive to the formation of a dense oxide layer, allowing the oxidizing medium to easily erode into the material. The thickness of the oxide layer after water-oxygen oxidation is 28.4 μm.
[0076] Comparative Example 5
[0077] The preparation process of the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic-based composite material in this comparative example 5 refers to Example 1, with the only difference being that in step (1), the mass ratio of SiC powder, Y2O3 powder, Al2O3 powder, carbon black, polyvinyl alcohol (binder) and ethanol is 45:18:2:10:5:55.
[0078] After testing, the Al2O3-RE2O3 synergistically modified high temperature water-oxygen corrosion-resistant silicon carbide ceramic-based composite material prepared in Comparative Example 5 has a strength retention rate of 76.7% after water-oxygen oxidation at 1400°C for 100 h, and the thickness of the oxidation layer after water-oxygen oxidation is 16.4 μm.
[0079] Comparative Example 6
[0080] The preparation process of the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic-based composite material in this comparative example 6 refers to Example 1, with the only difference being that in step (1), the mass ratio of SiC powder, Y2O3 powder, Al2O3 powder, carbon black, polyvinyl alcohol (binder) and ethanol is 45: 5: 15: 10: 5: 55.
[0081] After testing, the Al2O3-RE2O3 synergistically modified high temperature water-oxygen corrosion-resistant silicon carbide ceramic-based composite material prepared in Comparative Example 6 had a strength retention rate of only 68.3% after water-oxygen oxidation at 1400°C for 100 h, and the thickness of the oxidation layer after water-oxygen oxidation was 15.7 μm.
[0082] Figure 2 The RE2O3-Al2O3 modified SiC in Example 1 f / SiC composite microstructure. As can be seen from the figure, the white phase (RE2O3+Al2O3) is evenly dispersed in the composite matrix.
[0083] Figure 3 The RE2O3-Al2O3 modified SiC in Example 1 f / SiC composite surface morphology. As can be seen from the figure, a large number of crystalline phases are gathered on the surface of the oxide layer, isolating the water and oxygen medium, and the EDS results confirm that the crystalline phase is Y2Si2O7.
[0084] Figure 4 The RE2O3-Al2O3 modified SiC in Example 1 f SEM image of the SiC / SiC composite material after 1400 ℃ water-oxygen immersion for 100 h, where a is the microscopic morphology and b is the oxygen corrosion depth. It can be seen from the figure that the oxide layer on the surface of the material is thin and dense, and oxygen is suppressed in the surface area of the material.
[0085] Figure 5 The RE2O3-Al2O3 modified SiC in Example 1 f / SiC composite material and unmodified SiC in comparative example 1 f / SiC composite material strength retention rate after 100 h of water and oxygen. As can be seen from the figure, with the increase of water and oxygen temperature, the unmodified SiC f / SiC material bending strength retention rate decreased significantly, while RE2O3-Al2O3SiC f / SiC composites have significantly higher strength retention after water-oxygen corrosion.
[0086] Figure 6 For the YE2O3 modified SiC in Comparative Example 3 fThe microstructure of the / SiC composite material after 1400 ℃ water-oxygen immersion for 100 h. As can be seen from the figure, although there are a large number of Y2Si2O7 crystal phases aggregated in the oxide layer, there are many holes and cracks under the oxide layer.
[0087] Figure 7 For RE2O3-Al2O3 modified SiC in Comparative Example 6 f Microstructure of the SiC / SiC composite material after 1400 ℃ water-oxygen treatment for 100 h. As can be seen from the figure, a large amount of glass phase is gathered on the surface of the oxide layer, and there are a large number of holes on the surface of the oxide layer. The EDS results confirm that the glass phase is Y-Al-Si-O glass.
Claims
1. A method for preparing an Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic matrix composite material, characterized in that: include: (1) Mixing SiC powder, RE2O3 powder, Al2O3 powder, carbon black, a binder and a solvent to obtain a mixed slurry; (2) immersing the fiber preform into the mixed slurry, drying, curing, and pyrolyzing to obtain a carbon-containing porous preform; (3) The carbon-containing porous preform is subjected to silicon reactive infiltration treatment to obtain the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic matrix composite material.
2. The preparation method according to claim 1, characterized in that: In step (1), the RE2O3 powder is selected from one of Y2O3, Yb2O3, La2O3, Lu2O3, Ce2O3, Er2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3, Dy2O3, and Ho2O3.
3. The preparation method according to claim 1, characterized in that In step (1), the particle size of the SiC powder is 0.01 to 10 μm; the particle size of the RE2O3 powder is 0.01 to 10 μm; the particle size of the Al2O3 powder is 0.01 to 10 μm; and the particle size of the carbon black is 0.001 to 1 μm.
4. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of SiC powder, RE2O3 powder, Al2O3 powder, carbon black, binder and solvent in the mixed slurry is (30-70): (10-30): (5-10): (10-30): (5-10): (35-65).
5. The preparation method according to claim 1, characterized in that: In step (2), the fiber preform is a silicon carbide fiber preform; the structure of the silicon carbide fiber preform is at least one of a two-dimensional stitched braided structure, a three-dimensional needle-punched braided structure, a three-dimensional four-way braided structure, and a three-dimensional five-way braided structure; an interface layer is deposited on the surface of the silicon carbide fiber preform; the interface layer is one of pyrolytic carbon or boron nitride; and the thickness of the interface layer is 0.1 to 1.0 μm.
6. The preparation method according to claim 1, characterized in that: In step (2), the slurry is impregnated by at least one of ultrasonic impregnation, vibration impregnation, and negative pressure impregnation.
7. The preparation method according to claim 1, characterized in that In step (2), the curing temperature is 80 to 300°C and the curing time is 0.5 to 2 hours; The pyrolysis temperature is 500-1000°C and the time is 0.5-2 hours.
8. The preparation method according to claim 1, characterized in that In step (2), the open porosity of the carbon-containing porous preform is 5% to 30%.
9. The preparation method according to claim 1, characterized in that In step (3), the temperature of the silicon reactive infiltration treatment is 1400-1800° C., and the time is 0.1-5 hours.
10. An Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic matrix composite material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: In the Al2O3-RE2O3 synergistically modified high temperature water and oxygen corrosion resistant silicon carbide ceramic matrix composite material, the volume fraction of the silicon carbide fiber preform is 10-40%, the volume fraction of the SiC matrix is 30-60%, the volume fraction of the RE2O3 phase is 2-10%, and the volume fraction of the Al2O3 phase is 3-6%.
Citation Information
Patent Citations
Method for combinedly improving high-temperature water and oxygen corrosion resistance of SiCf / SiC composite material
CN109384475A
Method for improving high temperature water / oxygen erosion resistance of SiCf / Si-B-C self-healing ceramic matrix composite material
CN109836163A
Silicon carbide ceramic-based composite material resistant to high-temperature water and oxygen erosion and preparation method of silicon carbide ceramic-based composite material
CN115784749A
Anti-oxidation type silicon carbide wear-resistant plastic material as well as preparation method and application thereof
CN116283318A
SiCf / SiC ceramic-based composite material and preparation method thereof
CN118420348A